Answer:B
Step-by-step explanation: i think it is the only one observing something tell me if i am wrong though
Answer:
![\sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
Step-by-step explanation:
Answer:
answer is $819
Step-by-step explanation:
I did 1073+1108+x/3=1000 Let me know if this is wrong please !
Start by writing the system down, I will use
to represent ![f(x)](https://tex.z-dn.net/?f=f%28x%29)
![y=x^2-5x+3\wedge y=-3](https://tex.z-dn.net/?f=y%3Dx%5E2-5x%2B3%5Cwedge%20y%3D-3)
Substitute the fact that
into the first equation to get,
![-3=x^2-5x+3](https://tex.z-dn.net/?f=-3%3Dx%5E2-5x%2B3)
Simplify into a quadratic form (
),
![x^2-5x+6=0](https://tex.z-dn.net/?f=x%5E2-5x%2B6%3D0)
Now you can use Vieta's rule which states that any quadratic equation can be written in the following form,
![x^2+x(m+n)+mn=0](https://tex.z-dn.net/?f=x%5E2%2Bx%28m%2Bn%29%2Bmn%3D0)
which then must factor into
![(x+m)(x+n)=0](https://tex.z-dn.net/?f=%28x%2Bm%29%28x%2Bn%29%3D0)
And the solutions will be
.
Clearly for small coefficients like ours
, this is very easy to figure out. To get 5 and 6 we simply say that
.
This fits the definition as
and
.
So as mentioned, solutions will equal to
but these are just x-values in the solution pairs of a form
.
To get y-values we must substitute 3 for x in the original equation and then also 2 for x in the original equation. Luckily we already know that substituting either of the two numbers yields a zero.
So the solution pairs are
and
.
Hope this helps :)